Loss of air sacs improved hominin speech abilities. - de Boer, Bart (J Hum Evol, 2012)
In this paper, the acoustic-perceptual effects of air sacs are investigated. Using an adaptive hearing experiment, it is shown that air sacs reduce the perceptual effect of vowel-like articulations. Air sacs are a feature of the vocal tract of all great apes, except humans. Because the presence or absence of air sacs is correlated with the anatomy of the hyoid bone, a probable minimum and maximum date of the loss of air sacs can be estimated from fossil hyoid bones. Australopithecus afarensis still had air sacs about 3.3 Ma, while Homo heidelbergensis, some 600 000 years ago and Homo neandethalensis some 60 000 years ago, did no longer. The reduced distinctiveness of articulations produced with an air sac is in line with the hypothesis that air sacs were selected against because of the evolution of complex vocal communication. This relation between complex vocal communication and fossil evidence may help to get a firmer estimate of when speech first evolved.
Keywords: Air Sacs; Animals; Biological Evolution; Female; Hominidae; Humans; Male; Models, Biological; Speech